An heir claimed by Christmas - Connelly, Clare (Romance novelist) (Harlequin presents, 2020)
She can't deny him his heir ... but she won't surrender her heart! Dimitrios Papandreo once spent a desperate, passionate night with Annie Hargreaves. Knowing he couldn't offer the happily-ever-after she deserved, he's been trying to forget her ever since ... until he's told she's raising their son! Annie's speechless when Dimitrios arrives on her doorstep, declaring he knows her secret. He'll accept nothing less than marriage to claim his child! That means moving to Singapore and facing their electrifying connection ... Can Annie walk down the aisle this Christmas, knowing Dimitrios might never be capable of loving her?